Regular aerobic exercise ameliorates radiation-induced pulmonary fibrosis: An animal study - Da Bin Ko; Seungwoo Cha; Jae Yong Jeon; Su Ssan Kim; Won Kim; Sei Won Lee; Joongkee Min; Si Yeol Song; Seung Hak Lee (Clinical and Translational Radiation Oncology)
Background and purpose: A definitive treatment for radiation-induced pulmonary fibrosis (RIPF), a common side effect of radiation therapy for thoracic cancer, remains to be established. Pulmonary rehabilitation programs, including regular aerobic exercise, may ameliorate RIPF. However, a scientific basis supporting the protective effect of exercise against RIPF is lacking. Methods: Seven-week-old Sprague-Dawley rats were randomly allocated to the control (CON), training without irradiation (T), irradiation only (IR), and irradiation with training (IR + T) groups. Irradiation of the right lung was commenced at 40 Gy over five consecutive days, followed by regular aerobic exercise training using a treadmill for 7 weeks. The variables were assessed before and after irradiation. Pulmonary fibrosis was assessed using Masson’s trichrome (MT) staining and hydroxyproline (HYP) assay. Behavioral tests were conducted to evaluate functional changes. In addition, potential molecular mechanisms were explored. Results: The body weights of the rats in the IR and IR + T groups were lower than those in the other two groups. The Rota-rod test revealed significantly higher exercise capacity in the IR + T group compared to that in the IR group, which was closer to that in the CON group. MT staining and HYP assay revealed that the amount of fibrosis in the IR + T group was significantly lower than that in the IR group (collagen area (%): IR, 28.00 ± 7.51, n = 7; IR + T, 24.03 ± 6.93, n = 9; HYP concentration (μg/mg): IR, 0.80 ± 0.09, n = 7; IR + T, 0.47 ± 0.14, n = 9; p < 0.05). Superoxide dismutase activity in the IR + T group was higher than that in the IR group (IR, 84.02 ± 12.56, n = 7; IR + T, 100.55 ± 11.18, n = 9; p < 0.05). Conclusions: Regular aerobic exercise ameliorated RIPF in rats, suggesting its potential utility in pulmonary rehabilitation programs for patients undergoing thoracic radiation therapy.